A CONSTRUÇÃO DISCURSIVA DA IMAGEM DA ORGANIZAÇÃO PÚBLICA EM UM CONTEXTO REGIONAL POLÍTICO: O caso da UFABC - Castilho, Alessandra de (2014)
This research discusses how to build the image of an institution by means of speeches prepared by the organization and the national and regional press. Also studies the macro elements that can influence this construction, especially when the organization was installed in a regional context with strong political appeal. Also reflects on the social responsibility of media in building the organizational image. For a discussion that was held looking aligning practice to theory through the literature search by traversing subjects like public communication, speech and the press organizations in building the image, and also the analysis of particular case, the Universidade Federal do ABC. One Participant Observation was performed, since the researcher is embedded in the object searched. This research makes a contribution, especially for professionals and researchers in public communication, to assess to what degree can be perceived political influence in building the organizational image of public institutions. An analysis of how this University, who in 2013 completed seven years of activities was held is being perceived and exploited by the media and how was the influence of the political context in the media discourse. This survey was conducted through content analysis of printed online clipping the institution to identify general trends in media interest and segment topics. In this analysis was observed a clear relationship between the number of negative issues with the number of political quote. The periods in which the University was approached by the press for controversial issues such as high dropout rate and delay of works, were also periods in which there was a significant increase in political / partisan quotes. Finally, speech analysis and reports on selected articles which confronted the institutionally crafted with the reflected image in the media was performed. This work enabled to verify that the analyzed years, especially in 2010 when the presidential speech organization elections took place was built with the goal of reversing the negative image the media much more than build their own image.